The Urgency of Designing National English Curriculum for Elementary School in Indonesia - Sari Astuti; Muhammad Lukman (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
To propose the idea of designing national English curriculum for elementary school in Indonesia, a literature review as a research methodology in this study was conducted to reveal the urgency of teaching English to young learners, based on a number of previous studies on this issue, as the preparation for the future generation facing the era of globalization. The fact that English is the language of world trade and technology has benefit the countries in which English is taught since Elementary level with their national standardized curriculum, such as Singapore, Malaysia, and Brunei to grow rapidly. Contrast to their conditions, In Indonesia, although there are many positive responses from the society about introducing English since elementary school, based on National Curriculum 2013, the government has just allowed schools to teach English since junior high school. As a result, there are great numbers of elementary schools start teaching English to their students without necessarily developing proper curriculum or even having qualified teachers. Therefore, providing national English curriculum for elementary school is strongly required to give teachers and schools clear guideline and proper standard to teach English at early stage. It is expected that proper and nationally standardized English curriculum will help teachers and schools to teach English according to the student needs and capacity and build strong foundation for learning English on the next stage. Keywords: National English curriculum for elementary school, young learners, National Curriculum 2013